Hysteresis in magnetism for physicists, materials scientists, and engineers - Bertotti, Giorgio (Electromagnetism)
This book provides a comprehensive treatment of the physics of hysteresis in magnetism and of the mathematical tools used to describe it. Hysteresis in Magnetism discusses from a unified viewpoint the relationsof hysteresis to Maxwells equations, equilibrium and non-equilibrium thermodynamics, non-linear system dynamics, micromagnetics, and domain theory. These aspects are then applied to the interpretation of magnetization reversal mechanisms: coherent rotation and switching in magnetic particles, stochastic domain wall motion and the Barkhausen effect, coercivity mechanisms and magnetic viscosity, rate-dependent hysteresis and eddy-current losses. The book emphasizes the connection between basic physical ideas and phenomenological models of interest to applications, and, in particular, to the conceptual path going from Maxwells equations and thermodynamics to micromagnetics and to Preisach hysteresis modeling.